EDUCATION ON THE USE OF CHICKEN MANURE AND VOLCANIC ASH IN SHALLOT CULTIVATION - Ernitha Panjaitan (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study aims to determine the response of growth and production as well as the availability of silica to the application of chicken manure and volcanic ash in shallot plants (Allium ascalonicum l.). This study used a Randomized Group Design (RAK) with 2 factors. The first factor is chicken manure consisting of 4 levels, namely: A0 = Control (No chicken manure), A1 = 3.75 kg/plot (10 tons/ha), A2 = 7.5 kg/plot (20 tons/ha), A3 = 11.25 kg/plot (30 tons/ha). The second factor is volcanic ash consisting of 4 levels, namely: V0 = Control (No volcanic ash), V1 = 1.9 kg/plot (5 tons/ha), V2 = 3.8 kg/plot (10 tons/ha), V3 = 5.6 kg/plot (15 tons/ha). The results showed that chicken manure up to a dose of 11.25 kg/plot had a significant effect on leaf length, plant wet weight/sample, plant wet weight/plot, plant dry weight/sample, plant dry weight/plot, base saturation, C- organic, pH H2O, but had no significant effect on the number of tubers, CEC and Si availability in paddy fields. Volcanic ash dose treatment had no significant effect on all parameters observed. The interaction between the doses of chicken manure and volcanic ash had no significant effect on leaf length at 2, 3, and 5 weeks of planting, wet weight of plants/sample, dry weight of plants/sample, base saturation, C-organic, pH H2O, number of tubers, CEC and availability of Si in the paddy field, but had a significant effect on leaf length at 4 weeks of planting with the best combination that produced the highest average leaf length, namely treatment A2V3 (7.5 kg/plot of chicken manure and 5.62 kg/plot of volcanic ash): 5.62 kg/plot of volcanic ash), and significantly affected the wet weight of plants/plot and dry weight of plants/plot with the best combination that produced the heaviest average weight, namely treatment A1V2 (3.75 kg/plot of chicken manure : 3.75 kg/plot of volcanic ash).